Penentuan Hiposenter Dan Mekanisme Fokus Gempa Bumi MLv4,8 1 Januari 2015 Di Sekitar Sesar Matano - Muhammad Fawzy Ismullah Massinai; Muhammad Altin Massinai; Aulia Puji Astuti; Nurainun Sholihat Arifuddin (Universitas Muslim Indonesia, 2020)
Earthquake was recorded by BMKG on Thursday January 1, 2015 at 22:20:04.8 GMT or Friday January 2, 2015 at 06:20:04.8 Central Indonesia Time. Hypocenter located at 120.87 E, 2.22 S with depth of 17 km and magnitude MLv4.8. Purpose of this research is to study fault plane mechanism that cause this earthquake using hypocenter and focal mechanisms. This research used waveform MLv4.8 January 1, 2015 which recorded at BMKG earthquake observation stations. Waveform is processed to obtain arrival time P- and S-wave and polarity of arrival time P-wave. Method used to determine hypocenter is Geiger Method with input are arrival time P- and S-wave. Focal mechanisms determined using the first polarity of arrival P-wave and hypocenter from previous step. Hypocenter obtained from this research is located at 2.2073 S, 120.798 E and 10 km depth. RMS is 0.7391. Focal mechanism of this earthquake is oblique fault, is normal fault with left-lateral strike slip component. Parameters are strike 3120, dip 710 and rake -140. This result is consistent with Matano Fault type as a continuation of Palu-Koro Fault. MLv4.8 January 1, 2015 earthquake occurred because Matano Fault activity. Research results can provide a basis form earthquake hazard mitigation along Matano Fault zone.